Economic Analysis and Factors Influencing the Development of Tourism - TEMIRALIYEVA, Zubaira; ABDYKULOVA, Karlygash; BAIBASHEVA, Gulnara; SADYKOV, Zhassulan; NAKIPOVA, Gulmira; TOKAEVA, Layly (Journal of Environmental Management and Tourism, 2021)
The ongoing transformations in various aspects in the field of tourism services lead to an increase in the importance of tourism in the development of the national economy, which is due to a change in the mechanism of functioning of the tourism industry, a complex impact on the economy of other industries. Taking into account the factors affecting the development of tourism, it should be noted that the industry tourism has a synergistic effect: the quality of service improves, insurance companies are attracted, new segments of tourism are emerging, new routes are being developed.Development and support of the tourism industry, the development of competition and investment attractiveness depend on a wide range of factors reflecting the general state of the economic policy of the state and the position of state institutions, in connection with which the issues of developing the entrepreneurial climate, increasing investment attractiveness and, in general, the competitiveness of the tourism sector are one of the key directions of the state's economic policy.